Survey of geomorphic and morphotectonic indixes to assessment active tectonics in Abdoughi area, North east of Yazd, Central Iran - arash shrbi; Soheyla Beygi (تحقیقات کاربردی علوم جغرافیایی)
Morphotectonic is one of the new reconition methods of tectonic movements and earthquakes knowledge. Study and measurement of landscapes and forms which made by active tectonics are important objects in morphology science. Active tectonic movements have recorded in the morphology of rivers, drainages, alluvial fans and mountain fronts in a region. Research area is located between 55° 30' -57° 00' E and 32° 00' -33° 00' N in Central Iran structural zone. In this paper, we have studied geological map of Abdoughi and processed satellite images, digital elevation model (DEM), geomorphic and morphotectonic indices along the main faults. Also tectonic activities were measured in this area. The results of mountain- front sinuosity (Smf), ratio of valley-floor width to valley height (Vf) and ratio of valley width to valley height (V) indicate respectively: 1/15, 0/94 and 9/88 values. The displacement of the rivers, alluvial fans and triangular facets indicate tectonic activity during Quaternary along the faults. The morphotectonic evidences and seismicity data show which Abdoughi area is an active region.